Fabrication of circular cooling channels by cold metal transfer based wire and arc additive manufacturing. (September 2021) - Han, Shaohua; Zhang, Zhongzhong; Ruan, Pengxiang; Cheng, Shiwen; Xue, Dingqi
Additive manufacturing has been proven to be a promising technology for fabricating high-performance dies, molds, and conformal cooling channels. As one of the manufacturing methods, wire and arc additive manufacturing displays unique advantages of low cost and high deposition rate that are better than other high energy beam-based ones. This paper presents a preliminary study of fabricating integrated cooling channels by CMT-based wire and arc additive manufacturing process. The deposition strategies for fabricating circular cross-sectional cooling channels both in conformal and straight-line patterns have been investigated. It included optimizing the welding torch angle, fabricating the enclosed semicircle structure and predicting the collision between the torch and constructed part. The cooling effect test was also conducted on both the conformal cooling channel and straight-line cooling channel. The results affirmed a higher cooling efficiency and better uniform cooling effect of the conformal cooling channel than straight-line cooling channel.